Anti-tobacco groups in Balneario Camboriu (Santa Catarina, Brazil): immediate and long-term tobacco smoking cessation rate - Fernanda A. FRONZA; Ericks S. SOARES; Thiago M. SAKAE; Helena I. CIMAROSTI (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2023)
Introduction: Tobacco smoking causes millions of deaths every year and is a risk factor for chronic non-communicable diseases, leading to a significant socioeconomic impact worldwide. In Brazil, the primary healthcare services for smokers include cognitive-behavioural approaches and pharmacological treatment offered through anti-tobacco groups. Objective: Considering the importance of the antitobacco groups and the need for more studies about them, this study aimed to determine the immediate and long-term tobacco smoking cessation rate of anti-tobacco groups in the city of Balneário Camboriu, Santa Catarina (Brazil), and to verify the existence of variables associated with successful smoking cessation. Method: Data from 256 participants were analysed, between 2015 and 2016, and the tobacco smoking cessation rate was investigated by applying questionnaires to 152 participants who accepted to participate. Results: The immediate and long-term cessation tobacco smoking cessation rates were 59.4% and 32.9%, respectively. When analysing the medication use, we observed that the bupropion hydrochloride and transdermal nicotine combined treatment increased almost three times more the chance of immediate cessation success, while attending the four group meetings increased this chance by seven times more. Conclusion: Although the analysed long-term variables did not present an association with the maintenance of a nonsmoking status, our findings show the importance of anti-tobacco groups to achieve success and stop tobacco smoking.